Lecture_13 - = y ° r 2 − r 1 c 2 e r 2 t = y ° − r 1 y Since r 1 ° = r 2 as can solve For c 1 and c 2 as claimed.

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
4 MA 36600 LECTURE NOTES: MONDAY, FEBRUARY 16 Upon multiplying the frst equation by r 2 then by r 1 , we have the Following systems oF equations: r 2 c 1 e r 1 t 0 + r 2 c 2 e r 2 t 0 = r 2 y 0 r 1 c 1 e r 1 t 0 + r 2 c 2 e r 2 t 0 = y ° 0 ( r 1 r 2 ) c 1 e r 1 t 0 = y ° 0 r 2 y 0 r 1 c 1 e r 1 t 0 + r 1 c 2 e r 2 t 0 = r 1 y 0 r 1 c 1 e r 1 t 0 + r 2 c 2 e r 2 t
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: = y ° ( r 2 − r 1 ) c 2 e r 2 t = y ° − r 1 y Since r 1 ° = r 2 , as can solve For c 1 and c 2 as claimed....
View Full Document

This note was uploaded on 11/30/2011 for the course MATH 366 taught by Professor Edraygoins during the Spring '09 term at Purdue University-West Lafayette.

Ask a homework question - tutors are online